POTENSI CAMPURAN KECAMBAH BERAS COKLAT DAN KECAMBAH KEDELAI SEBAGAI MINUMAN FUNGSIONAL TINGGI SERAT DAN PROTEIN (Potential for Mixed Brown Rice Sprouts and Soybean Sprouts as Fuctional Beverage High Fiber and Protein) - Siti Aminah (Universitas Muhammadiyah Semarang, 2010)
Brown rice sprouts and soybean sprouts potential as a functional beverage ingredients. This study aims to measure the levels of protein and fiber beverage from a mixture of brown rice sprouts and soybean sprouts, and knowing the nature organoletiknya. The materials used are brown rice, local soybean, spices and sugar. The experimental design in this study was completely randomized design with sprouted flour concentration factor with three replicates. The highest protein content in the treatment of mixing flour and sprouted brown rice seedling soybean: 10:90% as much as 35.20 g% is the lowest protein content in the treatment of 50:50% as much as 18.87 g%. The highest fiber content in the treatment of 30:70% as much as 0:35 g%, while the lowest levels in the treatment of 50%: 50% as much as 0.027 g%. Rendement sprouted brown rice flour as much as 80% and 67% soybean sprout flour. Organoletik score highest on treatment E: 50:50%. Statistical analysis showed no treatment effect on protein content, and organoleptic, but did not affect the fiber content. Key words: Brown Rice, Soybean, Sprout, Functional Beverage